THE NUTRITIONAL CARRYING-CAPACITY OF 4 MEDITERRANEAN HABITATS FOR FALLOW DEER (DAMA-DAMA) - Focardi, S; Poli, B M; Tinelli, A (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 1995)
The assessment of the trophic value of the most consumed feed by fallow deer in a coastal mediterranean landscape (Rubus ulmifolius, Cistus salvifolius, Phyllirea latifolia, Quercus ilex and graminoids) was based on in vitro digestibility trials, performed throughout the year (1 set of samples per season) using rumen inocula from wild fallow deer from the Preserve of Castelporziano, collected simultaneously with the vegetal samples. Moreover, in vivo digestibility coefficients have been estimated by using standard feed (for fallow deer) of known in vivo digestibility. Using the digestibility coefficients, the metabolizable energy yield of studied forage items was computed. Information about plant biomass, structure of fallow deer population, metabolizable energy yields, estimates of forage intake and energy requirements were combined using the model presented by Hobbs and Swift (1985) to evaluate the nutritional carrying capacity of four typical mediterranean habitats (natural evergreen oak wood, scrub mixed plantations of Quercus ilex and Pinus pinea, open pastures). Spring represents the most favourable situation, while summer, autumn and winter exhibit similar values of carrying capacity of about 15-20 deer/100 ha. Mixed plantations of Pinus pinea and Q. ilex seem to be the most productive condition for fallow deer.
APS
Keywords: Cistus salvifolius; digestibility; fallow dear; mediterranean landscape; Phyllirea latifolia; Quercus ilex; Rubus ulmifolius; trophic value